2020
DOI: 10.1093/jscr/rjaa179
|View full text |Cite
|
Sign up to set email alerts
|

Cystic lymphangioma in adult: a case report and a review of the literature

Abstract: Cystic lymphangioma (CL) in adult is a very rare pathology. Its etiology remains unclear, but it is supposed to be congenital or to be a result of obstruction and lymph fluid retention of developing lymphatic vessels. It generally occurs in the head and neck region, probably because of the rich lymphatics in this area. It can be easily misdiagnosed with other cervicofacial masses. We present the case of a 56-year-old-female presented with a right-sided painless cervical swelling. Ultrasonography and magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 9 publications
0
34
1
2
Order By: Relevance
“…Role of Fine needle aspiration cytology (FNAC) in diagnostic workup of CH is criticised due to risk of infection and bleeding associated with the procedure. Walter Colangeli et al reported in their study that FNAC had a low diagnostic value and it did not modify the treatment approach [14,22]. In the described case, FNAC was performed as initial workup before the patient reported at our centre and hence it was not repeated due to its limited yield in diagnosis.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Role of Fine needle aspiration cytology (FNAC) in diagnostic workup of CH is criticised due to risk of infection and bleeding associated with the procedure. Walter Colangeli et al reported in their study that FNAC had a low diagnostic value and it did not modify the treatment approach [14,22]. In the described case, FNAC was performed as initial workup before the patient reported at our centre and hence it was not repeated due to its limited yield in diagnosis.…”
Section: Discussionmentioning
confidence: 86%
“…CH is rare in adult and very few cases have been reported in literature [4,5,7,[10][11][12][13][14][15][16][17][18][19][20][21]. Development of CH in adulthood is caused by delayed proliferation of cell rests with infection, trauma, or iatrogenic stimuli as being the predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Histopathological assessment is necessary to confirm diagnosis in adults. 12 In the absence of dysphagia or breathing difficulty, a stepwise diagnostic progression would be reasonable. This may include ED referral to the primary physician or otolaryngology for more definitive imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cases suggest surgical excision as the preferred treatment modality in adults to mitigate tumor recurrence. 12,13 Decisions regarding treatment strategies will depend on location and associated symptoms as well. For instance, patients suffering from dysphagia, dyspnea, or other vital structures at risk often require surgery.…”
Section: Discussionmentioning
confidence: 99%